2015
DOI: 10.1109/tit.2015.2402163
|View full text |Cite
|
Sign up to set email alerts
|

When Are Dynamic Relaying Strategies Necessary in Half-Duplex Wireless Networks?

Abstract: Abstract-In this paper we study a simple question: when are dynamic relaying strategies essential in optimizing the diversitymultiplexing tradeoff (DMT) in half-duplex wireless relay networks? This is motivated by apparently two contrasting results even for a simple 3 node network, with a single half-duplex relay. When all channels in the system are assumed to be independent and identically fading, a static schedule where the relay listens half the time and transmits half the time combined with quantizemap-and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…Also on the contrary to previous works using orthogonal protocol, our protocol is non-orthogonal where the users and the relay can transmit simultaneously. We have designed a low complexity coset decoder for the destination which jointly decodes multiple users' messages from the users' † The proposed scheme may be further improved by optimally scheduling the relay's listening time (Phase 1) and transmit time (Phase 2) as [17]. However, this dynamic scheduling requires highly precise synchronization between nodes and this direction is beyond the scope of our paper.…”
Section: Discussionmentioning
confidence: 99%
“…Also on the contrary to previous works using orthogonal protocol, our protocol is non-orthogonal where the users and the relay can transmit simultaneously. We have designed a low complexity coset decoder for the destination which jointly decodes multiple users' messages from the users' † The proposed scheme may be further improved by optimally scheduling the relay's listening time (Phase 1) and transmit time (Phase 2) as [17]. However, this dynamic scheduling requires highly precise synchronization between nodes and this direction is beyond the scope of our paper.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we often expect to see an increase in the capacity of the network when the half-duplex relays are replaced with full-duplex ones. Regardless of this fact, for certain multiplexing gains and average SNR exponents of different links, the two networks perform the same in terms of DMT [6], [7], [25].…”
Section: B Proofsmentioning
confidence: 99%
“…The authors in [1] studied an opportunistic DDF for MARC where the relay selection is based on source-to-destination channel gain and have proved that the scheme achieves optimal DMT only at lower multiplexing gains. In [5], DMT of DDF protocol for generalized channels has been derived. It is shown that DDF fails to achieve optimal performance in higher multiplexing gain regime.…”
Section: Motivationmentioning
confidence: 99%